Pelatihan dan Pendampingan Pembukuan Keuangan Digital Menggunakan Aplikasi BukuWarung pada Toko Beras Laris - Irsan Herlandi Putra (Institut Teknologi dan Bisnis Semarang, 2024)
Many Micro, Small and Medium Enterprises (MSMEs) still use manual recording in today's digital era. MSME businesses must realize the importance of digital financial records through bookkeeping applications. This can help MSME owners record financial transactions and make it easier for them to recap the sales of goods they sell through the BukuWarung application. The purpose of this community service is to conduct training and mentoring using the simple BukuWarung application to record financial transactions. This paper method uses a qualitative methodology. MSME owners of Selling Rice Shops in Soreang District, Bandung Regency participated in this training. This activity equips MSME owners with the ability to use the BukuWarung application, make transactions in it, find out the cost of goods sold, record financials, and make financial reports.